Overview of Public Knowledge about Hypertension: A Study at Suppa Health Center, Pinrang Regency - Rahman, Abd.; Anugrah, Sukma; Natsir, M.; Bahrudin; Nuralamsyah, Muhammad; Hasan, Edi (CV. Literasi Publikasi Indonesia, 2025)
Hypertension is one of the most prevalent non-communicable diseases and remains a major concern in public health. Public knowledge about hypertension plays a crucial role in its prevention and management. Objective This study aimed to describe the level of public knowledge about hypertension in the working area of the Suppa Public Health Center, Pinrang Regency. Methods This research used a quantitative approach with a descriptive design. A total of 47 respondents were selected using Slovin’s formula from the population in the Suppa Health Center area. Data were collected using a closed-ended questionnaire with dichotomous choices (Yes/No). Data analysis was performed using descriptive statistics in the form of frequency and percentage distributions. Results The study revealed that the majority of respondents had good knowledge of hypertension, with 43 people (91.5%) categorized as having good knowledge and 4 people (8.5%) with sufficient knowledge. Respondents’ knowledge was influenced by their education level, information sources, and media exposure. Conclusion Most of the community members in the Suppa Health Center area have good knowledge of hypertension. This reflects the effectiveness of ongoing health education efforts. Continued and enhanced health promotion is recommended to maintain and improve community awareness.